Optimized scheduling mechanism based on IEEE 802.1Qch standard in time-sensitive networking - Hongrui NIE; Shaosheng LI; Yong LIU (Tongxin xuebao)
To address the problem of complex gating planning for generic time-aware shaper (TAS), a traffic scheduling mechanism of adaptive queue buffer size and hardware time slot length was proposed with the help of IEEE 802.1Qch standard.Taking traffic and network characteristics into account, a mixed integer linear programming routing and scheduling model was formulated to maximize the number of time-sensitive flows mapped to the target network and then further improve the network scheduling capability by balancing the traffic carried by each scheduling time slot.Moreover, the impact of traffic and network features on queue buffer and hardware scheduling time slot was obtained through different scenarios.Simulation results show that the proposed method could successfully deploy thousands of time-sensitive flows for solving the scheduling problem in local area networks, and can improve the scheduling success rate by up to 28% compared with other algorithms with feasible execution time.